2008
DOI: 10.1364/ao.47.002458
|View full text |Cite
|
Sign up to set email alerts
|

Observation of nanoparticle internalization on cellular membranes by using noninterferometric widefield optical profilometry

Abstract: We demonstrate the observation of gold-nanoparticle internalization in membranes of living cells by using noninterferometric widefield optical profilometry (NIWOP). The NIWOP technique can trace the height of an 80 nm gold particle on the membrane by calibrating the change of light intensity scattered from the particle along the optical axis. On the membrane, the depth resolution based on the scattering signal is similar to that based on the reflection signal, nearly 20 nm. Comparing the heights of the nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…From this study, we found that direct luminescence‐based imaging of GNPs can hold a valuable and promising position in understanding their accumulation kinetics and distribution of GNPs at the intra‐organ level. We anticipate that the techniques demonstrated in the current study could extend the longitudinal in vitro studies 43, 44 to an in vivo setting whereby one could understand the targeting kinetics (i.e., cell internalization, particle transport, and cell‐specific targeting) in a more realistic solid tumor environment. In turn, this information will be valuable to develop models for generating thermal dosimetry of GNPs in therapeutic settings.…”
Section: Discussionmentioning
confidence: 98%
“…From this study, we found that direct luminescence‐based imaging of GNPs can hold a valuable and promising position in understanding their accumulation kinetics and distribution of GNPs at the intra‐organ level. We anticipate that the techniques demonstrated in the current study could extend the longitudinal in vitro studies 43, 44 to an in vivo setting whereby one could understand the targeting kinetics (i.e., cell internalization, particle transport, and cell‐specific targeting) in a more realistic solid tumor environment. In turn, this information will be valuable to develop models for generating thermal dosimetry of GNPs in therapeutic settings.…”
Section: Discussionmentioning
confidence: 98%
“…The depth positioning accuracy of the liposomes is thus about 17 nm. More details about the calibration of axial positions of scattering particles by the NIWOP technique can be found in a previous publication (Wang et al, 2008).…”
mentioning
confidence: 99%